Annotated catalogue of the click-beetle tribe Dimini (Coleoptera: Elateridae: Dendrometrinae) - Kundrata, Robin; Musalkova, Marketa; Kubaczkova, Magdalena (Zootaxa, 2018)
An annotated catalogue of the tribe Dimini (Coleoptera: Elateridae: Dendrometrinae) is presented. Altogether, 273 extant species are classified in 11 genera: Brancuccia Schimmel & Platia, 1991 (eight species), Csikia Szombathy, 1910 (eight spp.), Dima Charpentier, 1825 (77 spp.), Neocsikia Ôhira & Becker, 1972 (two spp.), Neodima Schimmel & Platia, 1992a (two spp.), Paracsikia Schimmel & Platia, 1991 (seven spp.), Parapenia Suzuki, 1982b (14 spp.), Penia Laporte, 1838 (108 spp.), Platiana Schimmel, 1993 (34 spp.), Pseudocsikia Schimmel & Platia, 1991 (10 spp.), and Sabahdima Schimmel & Platia, 1993 (three spp.). The only fossil genus included in this tribe is monotypic Alaodima Dolin, 1980. Dimini are distributed in the Palaearctic and Oriental Regions. For each taxon we provide synonyms, information on types, type localities, distribution, and bibliography. The lectotype of Penia apicalis Fleutiaux, 1936 is here designated in order to fix the identity of the species for future studies. Penia impressifrons Schimmel, 1993 from Vietnam is synonymized with Ceroleptus sulcatus (Fleutiaux, 1903), a representative of Elateridae: Oxynopterinae.